The Effect of Surgical Treatment of Morbid Obesity On Functional Capacity and Risk Fators For Cardiovascular Diseases - Manojlović, Andrea B; Malešević, Andrea Lj; Nedeljković, Ivana (Medicinski podmladak, 2017)
Introduction: Morbid obesity is associated with elevated risk of cardiovascular disease (CVD). Bariatric surgery is the most effective weight loss method for morbidly obese patients. Aim: To examine the effect of surgical treatment of morbid obesity on functional capacity and risk factors for CVD. Material and Method: In a group of 56 morbidly obese patients Body Mass Index (BMI), functional capacity and risk factors for CVD were compared before and after laparoscopic gastric bypass surgery. BMI was derived from the patients’ weight and height. Functional capacity parameters (peak VO2 and VE/VCO2 slope) and systolic (SBP) and diastolic (DBP) blood pressure were obtained during ergospirometry testing. Data on risk factors was acquired from medical histories and laboratory analyses. Results: A statistically significant difference was found in peak VO2 (p<0.0001) and VE/VCO2 slope (p =0.003) before and 6 months after the surgery. Resting SBP significantly decreased (p=0.017), as did SBP in maximal effort (p<0.0001). Similar results were observed when comparing resting and maximal effort DBP (p<0.0001 and p=0.002, respectively) before and after the surgery. Risk factors for CVD improved – hypercholesterolemia (12,5% vs 9%), diabetes (37% vs 19,6%) and hypertension (48,2% vs 33%). Conclusion: Morbidly obese patients showed an improvement of functional capacity, as well as in the risk factors for CVD 6 months following laparoscopic gastric bypass surgery. Key words: morbid obesity, surgery, functional capacity